Correction: Noble metal supported hexagonal boron nitride for the oxygen reduction reaction: a DFT study. Issue 1 (30th November 2018) - Back, Seoin; Siahrostami, Samira
Abstract : Correction for 'Noble metal supported hexagonal boron nitride for the oxygen reduction reaction: a DFT study' by Seoin Back et al., Nanoscale Adv., 2019, DOI: ; 10.1039/c8na00059j .